Progetto AMOR: quando la tecnologia incontra i Beni Culturali - Dore, Nicole (Archeomatica, 2022)
AMOR project focuses on the development of pre-commercial services addressed to the Institutions responsible for the conservation and the valorisation of the Cultural Heritage. Services, developed both for Safeguard and Fruition, will be tested at the Ancient Baths of Caracalla and on Aurelian walls, that will be surveyed with several technologies for the detection of superficial (satellites, UAV) or subsuperficial (GPR) damages/anomalies affecting them. Fruition services will offer to tourists a mobile app equipped with Institutional approved contents and with Mixed Reality experience (3D model) directly available on personal mobile devices. Moreover, the anonymous (previously authorised) tracking of tourists will allow to obtain further information useful for safeguard aspects.